Protocol to quantify and characterize contact between T cells and antigen-presenting cells in the antigen-draining lymph nodes of mice using flow cytometry - Naoya Tatsumi; Alejandro Davila-Pagan; Yosuke Kumamoto (STAR Protocols, 2022)
Summary: Physical contact between T cells and antigen-presenting cells (APCs) is essential for priming antigen-specific T cells, but quantitating the antigen-dependent T cell-APC contact can be laborious. Here, we present a simple flow-cytometry-based protocol for quantitating T cell-APC contacts in the antigen-draining lymph node in mice immunized with ovalbumin (OVA). This protocol quantifies the contact between adoptively transferred OVA-specific TCR transgenic CD4T (OT-II) cells and dendritic cell (DC) subsets. This approach can be applied to other types of intercellular interactions between T cells and APCs.For complete details on the use and execution of this protocol, please refer to Tatsumi et al. (2021).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.